Design, Control, and Analysis of a 3-Degree-of-Freedom Kinematic–Biologically Matched Hip Joint Structure for Lower Limb Exoskeleton - Yuntian Wang; Xiuyuan Wu; Yifan Fang; Keisuke Osawa; Kei Nakagawa; Shintaro Yamasaki; Eiichiro Tanaka (Machines)
The increasing demand for rehabilitation and walking assistive devices driven by aging populations has promoted the development of a novel hip joint structure. This design aims to enhance the functionality of lower limb exoskeletons by eliminating the kinematic mismatch with the human’s biological hip. The design utilizes three 1-DOF (Degree of Freedom) rotational joints to replicate natural hip movement. By integrating IMU data, motor compensation is dynamically made to facilitate a more natural gait. Experimental results indicate improved hip joint angles and enhanced user comfort, presenting a promising solution for better walking assistance for elderly individuals.